Improving Social CRM through eletronic word-of-mouth: a case study of ReclameAqui - Almeida, Gustavo R. T. de; Cirqueira, Douglas Rocha; Lobato, Fábio M. F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
The ways of relationship between companies and customers have changed dramatically due to web-users engagement with Online Social Networks, impacting on the way consumers make purchase decisions. As a consequence, this phenomenon brought up a new concept, the Social Customer Relationship Management. In this context, Electronic Word-of-Mouth plays a significant role since customers are more exigent and having easy access to steadily more information about products, services and brands reputation. However, many reputation platforms do not provide an interface for automatic data collection. Thus, these data are not used in business decision making. Aiming to fill these gaps we propose an automatic data retrieval and analysis methods to knowledge extraction from Electronic Word-of-Mouth platforms, providing more reliability to the decision-making processes. The analysis consists in topic modeling using Latent Dirichlet Allocation to identify most frequent complaints and their correlations. Both, the data retrieval method and the analysis method are platform independent. A well-known reputation platform in Brazil was used to evaluate our proposal, the ReclameAqui.